2009
DOI: 10.1159/000224782
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab to Treat Acute Central Serous Chorioretinopathy: Short-Term Effect

Abstract: Aims: To report the beneficial effect of intravitreal bevacizumab (Avastin) injection in patients with acute central serous chorioretinopathy. Methods: Ten eyes of 10 patients with acute central serous chorioretinopathy received an intravitreal bevacizumab (1.25 mg/0.05 ml) injection. At baseline and follow-up visits patients had best corrected visual acuity (BCVA), IOP assessment, dilated fundus examination and OCT imaging. Main outcome measures were the resolution of neurosensory detachment, improvement in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 51 publications
(29 reference statements)
1
41
0
Order By: Relevance
“…19,40 Recently, anti-VEGF antibody has been used in CSC as an off-label method. [1][2][3][22][23][24]28,30,32,33,[41][42][43] Bevacizumab is a recombinant humanized full-length monoclonal antibody of VEGF that penetrates the retina and is transported into the photoreceptor outer segments, RPE, and choroid after intravitreal injection. 44 The half-life of bevacizumab in the vitreous is 5.6 days, and it remains in the eye for 4 to 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19,40 Recently, anti-VEGF antibody has been used in CSC as an off-label method. [1][2][3][22][23][24]28,30,32,33,[41][42][43] Bevacizumab is a recombinant humanized full-length monoclonal antibody of VEGF that penetrates the retina and is transported into the photoreceptor outer segments, RPE, and choroid after intravitreal injection. 44 The half-life of bevacizumab in the vitreous is 5.6 days, and it remains in the eye for 4 to 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Most case series reported no specific complications, although there is always some risk of postinjection endophthalmitis. 49 Most studies reported that IVB might be effective in terms of improving visual acuity and reducing CMT without significant complications and can be considered an optional intervention, 1,2,23,24,28,32,33 but these conclusions should be interpreted cautiously owing to the self-limiting nature of acute and even in chronic CSC. Moreover, it should be noted that the aqueous humor and plasma levels of VEGF were not significantly increased in patients with CSC compared with the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations